Combination of the PI3K inhibitor Idelalisib with the conventional cytostatics cytarabine and dexamethasone leads to changes in pathway activation that induce anti-proliferative effects in B lymphoblastic leukaemia cell lines - Kohrt, Lisa-Madeleine; Gladbach, Yvonne S.; Ernst, M.; Hamed, M.; Roolf, C.; Sender, S.; Beck, J.; Schütz, E.; Fischer, Sarah; Struckmann, Stephan; Junghanss, C.; Fuellen, G.; et al. (Cancer cell international, 2020)
Background: The introduction of combined conventional cytostatics and pathway-specific inhibitors has opened new treatment options for several cancer types including hematologic neoplasia such as leukaemias. As the detailed understanding of the combination-induced molecular effects is often lacking, the identification of combination-induced molecular mechanisms bears significant value for the further development of interventional approaches. Methods: Combined application of conventional cytostatic agents (cytarabine and dexamethasone) with the PI3K-inhibitor Idelalisib was analysed on cell-biologic parameters in two acute pro-B lymphoblastic leukaemia (B-ALL) cell lines. In particular, for comparative characterisation of the molecular signatures induced by the combined and mono application, whole transcriptome sequencing was performed. Emphasis was placed on pathways and genes exclusively regulated by drug combinations. Results: Idelalisib + cytostatics combinations changed pathway activation for, e.g., “Retinoblastoma in cancer”, “TGF-b signalling”, “Cell cycle” and “DNA-damage response” to a greater extent than the two cytostatics alone. Analyses of the top-20 regulated genes revealed that both combinations induce characteristic gene expression changes. Conclusion: A specific set of genes was exclusively deregulated by the drug combinations, matching the combination-specific anti-proliferative cell-biologic effects. The addition of Idelalisib suggests minor synergistic effects which are rather to be classified as additive.